Blended Learning as an Emerging Approach to Teacher Education in Higher Education in Sri Lanka: Lessons from a State-of-the-Art Review - Vithanapathirana, M. (My University, 2021)
Although blended learning in higher educat ion is well researched, the emphasis on blended learning in teacher education is relatively limited. Blended teacher education is an emerging approach within the State higher education sector in Sri Lanka. This article presents a review of empirical studies from recent global literature on blended learning in teacher education in the higher education sector. The review addresses three research questions: a) the nature of the research publications, b) themes and sub-themes addressed in the studies and c) future directions for the design of blended learning and research. With a systematic protocol of selection and a set of inclusion and exclusion criteria, 54 empirical research articles were selected as the sample for this state-of-the-art review. Twenty-four countries were represented in the sample. The majority of the articles were on pre-service teacher education and the research design commonly used was quantitative. A thematic analysis of the research articles identified six broad themes. The discussion on each theme and its sub-themes provides lessons from global research on blended learning and the transfer of knowledge. Future research, if focused more on interventionist designs, would help develop successful student-centered practices in blended learning for teacher education within higher education.
Keywords: Blended learning; higher education; teacher education; state-of-the-art; thematic analysis